2017
DOI: 10.1111/eos.12359
|View full text |Cite
|
Sign up to set email alerts
|

Oral problems and quality of life of preschool children: self‐reports of children and perception of parents/caregivers

Abstract: The purpose of this study was to evaluate the association between oral health problems and oral health-related quality of life (OHRQoL) of preschool children according to both self-reports and the reports of parents/caregivers. A school-based, cross-sectional study was conducted with 769 preschool children and their parents/caregivers. The OHRQoL was evaluated using the Scale of Oral Health Outcomes for Five-Year-Old Children (SOHO-5). Based on logistic regression for complex samples, the following variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 28 publications
3
49
1
2
Order By: Relevance
“…It is possible that children with white spots on their anterior teeth may perceive a negative esthetic effect. This finding is also described in a previous study, although no such association was found in the perception of parents/caregivers (Perazzo et al, 2017b). This may demonstrate that parents/caregivers perceive oral problems in small children only in the presence of pain, which underscores the importance of studies that also evaluate children’s perceptions to gain a better understanding of OHRQoL in young children.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…It is possible that children with white spots on their anterior teeth may perceive a negative esthetic effect. This finding is also described in a previous study, although no such association was found in the perception of parents/caregivers (Perazzo et al, 2017b). This may demonstrate that parents/caregivers perceive oral problems in small children only in the presence of pain, which underscores the importance of studies that also evaluate children’s perceptions to gain a better understanding of OHRQoL in young children.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have also demonstrated such associations, reporting that these conditions may be related to impairments with regard to functional, esthetic and social aspects (Kramer et al, 2013; Gomes et al, 2014; Abanto et al, 2014; Guedes et al, 2014; Perazzo et al, 2017b; Abanto et al, 2018). It is also possible that these relationships were due to the associated symptoms.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations